Toxicological effects of the Morinda citrifolia L. fruit extract on maternal reproduction and fetal development in rats - Leal-Silva, Thaís; Souza, Maysa Rocha [UNESP]; Cruz, Larissa Lopes [UNESP]; Moraes-Souza, Rafaianne Queiroz [UNESP]; Paula, Verônyca Gonçalves [UNESP]; Soares, Thaigra Sousa; Dela Justina, Vanessa; Giachini, Fernanda Regina; Damasceno, Débora Cristina [UNESP]; Américo, Madileine Francely; Volpato, Gustavo Tadeu (Taylor & Francis, 2022)
Morinda citrifolia L., also known as Noni, is widely used plant in folk medicine for various therapeutic purposes. However, reports on its effects during pregnancy are limited. Therefore, the objective of this study was to evaluate the effects of the M. citrifolia fruit extract on maternal performance and fetal development during pregnancy in rats. Pregnant Wistar rats (n = 12/group) were treated from gestational days (GD) 0–21 with water (control group) or the aqueous extract of M. citrifolia fruit at doses of 200, 400, or 750 mg/kg, orally. During pregnancy, clinical signs of toxicity, maternal weight, feed intake, and water consumption were noted. On GD 21, the rats were anesthetized and blood was collected to evaluate various biochemical parameters. During laparotomy, reproductive performance parameters were recorded, and fetuses were weighed and the anomalies analyzed. Reduced placental efficiency and fetal growth restriction were observed in the group treated with 400 mg/kg of M. citrifolia extract. The highest dose (750 mg/kg) augmented aspartate aminotransferase concentration and preimplantation losses, while reducing the number of live fetuses. Furthermore, both doses (400 and 750 mg/kg) of the plant extract caused fetal anomalies. In conclusion, consumption of high doses of the M. citrifolia aqueous extrac during pregnancy leads to maternal hepatotoxicity, anti-implantation effects, intrauterine growth restriction and fetal abnormalities, indicating that the plant fruit extract can be harmful to both the mother and the fetus.
Keywords: anti-implantation; maternal toxicity; Noni; rats; teratogenicity